TRIAL OF NEEM OIL (AZADIRACHTA INDICA) AS BASIC COMPOUND OF ELECTRIC LIQUID VAPORIZER AGAINST AEDES AEGYPTI MORTALITY - Diptyanusa, Ajib; Satoto, Tri Baskoro Tunggul; Hadianto, Tridjoko (Lembaga Penelitian Universitas YARSI, 2017)
Dengue Hemorrhagic Fever (DHF), commonly caused by Aedes aegypti mosquito bites, has been one of the world?s major concern for progressively increasing incidence. To prevent further increase in DHF incidence, an effective yet safe vector control method is needed. One of the most common method of vector control in Indonesia is using electric liquid vaporizer. Basic compounds which are less toxic to humans and less resistance-producing to mosquitoes are preferred, without neglecting its ability in killing mosquitoes. Neem trees (Azadirachta indica) could be easily found in many areas in Indonesia, mainly functioning as shading trees. Leaves and seed of neem tree may contain active compound used as natural insecticides, azadirachtin. The research aims to identify killing effect of neem oil as basic compound of electric liquid vaporizer against Aedes aegypti. Research subjects were 275 Aedes aegypti mosquitoes, aged 2-5 days. Subjects were divided into 3 groups: group A (negative control), group B (100% neem oil), and group C (0.001% d-allethrin as positive control). Knockdown time (KT1, KT50, KT95, KT100) and 24-hours mortality were observed. Test replications were done 3 times. The results showed that pure neem oil (Azadirachta indica) has no direct killing effect against Aedes aegypti. Further research is encouraged regarding identification of adulticide characteristics of azadirachtin and other active compounds of neem oil, such as nimbidin and nimbin.